METODE PEMBELAJARAN KESENIAN GENDANG BELEQ DI SMP N 3 MASBAGIK - Ashwan Kailani; Alwan Hafiz; Teguh Bayu Alam (TAMUMATRA, 2026)
Cultural arts education plays a vital role in fostering creativity and preserving local culture; however, in practice, it is often dominated by theoretical approaches, resulting in a learning experience that falls short of being optimal for students. One potential solution is the implementation of clear teaching methods in traditional music education, such as Gendang Beleq. This study aims to describe the teaching methods for traditional Gendang Beleq music among seventh-grade students at SMP Negeri 3 Masbagik and to identify supporting and inhibiting factors in the learning process. This study employs a qualitative approach with a descriptive design and a case study framework. The research subjects include the Arts and Culture teacher and seventh-grade students selected through purposive sampling. Data collection techniques included observation, interviews, and documentation. The results indicate that several methods effectively foster students’ understanding of Gendang Beleq—both theoretically and practically—including the lecture method, demonstration method, and drill method. This study contributes to the development of practice-based cultural arts education and supports the preservation of traditional arts through formal education.